Implementasi Media Game Digital Edukatif Wordwall pada Mata Pelajaran Pendidikan Pancasila di SMA Negeri 2 Kota Pasuruan - Damayanti, Ayu Maya; Nurdiana, Rina; Sagita, Risa Dewi (Universitas PGRI Semarang, 2024)
Pancasila Education plays a strategic role in shaping the character and national values of young generations. However, in the increasingly digital era, students' interest in this subject tends to decline due to teaching methods perceived as less engaging and interactive. Leveraging digital technology in learning is a relevant solution to address this challenge. One innovative approach that can be applied is the use of digital educational games such as Wordwall. Wordwall enables teachers to create interactive quizzes that support the learning process in a fun, effective, and digital-based manner. This research was conducted at SMA Negeri 2 Pasuruan City to examine the implementation of Wordwall in improving student learning outcomes in Pancasila Education. The objective of the study is to measure the extent to which the use of Wordwall can enhance students' learning motivation, conceptual understanding, and critical thinking skills. Furthermore, this research evaluates teachers' perceptions of Wordwall's effectiveness in the learning process. This study is expected to contribute to the development of innovative learning models, particularly in Pancasila Education. The findings are also anticipated to serve as a reference for teachers, schools, and policymakers in improving the quality of education in Indonesia, while also encouraging the optimal utilization of digital technology in education. Hence, it is hoped that students' interest and learning outcomes in Pancasila Education will increase significantly.